2006
DOI: 10.1080/10428190500254299
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pyoderma gangrenosum as the presenting sign of fatal acute myelogenous leukemia

Abstract: Bullous pyoderma gangrenosum begins as a bulla, nodule or nonulcerated erythematous plaque that blisters or ulcerates to form a superficial ulcer surrounded by a hemorrhagic, bullous border, which is surrounded by a blue-gray halo. Bullous pyoderma gangrenosum is most commonly associated with hematologic malignancies, specifically, acute myelogenous leukemia (AML). We report a patient whose initial presentation with bullous pyoderma gangrenosum prompted the appropriate diagnostic evaluation and confirmation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
0
17
0
4
Order By: Relevance
“…In IBD, classic and pustular PGs are the subtypes most frequent; whereas in myeloproliferative diseases, bullous PG is the most common variant. 69,70 Vegetans PG is usually not associated with any systemic diseases.…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
“…In IBD, classic and pustular PGs are the subtypes most frequent; whereas in myeloproliferative diseases, bullous PG is the most common variant. 69,70 Vegetans PG is usually not associated with any systemic diseases.…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
“…34,35 Atypical and bullous types of PG are often associated with hematologic disorders and have been noted as a presenting sign of leukemia with some cases overlapping with Sweet syndrome. 32,[36][37][38][39][40][41][42] In a review of literature, around 35% of patients with postoperative PG had an associated systemic disease or a personal history of PG, with the majority of patients not having a predisposing comorbidity except surgery. 3,4 This is a greater systemic disease association compared with our cohort of 22% of postoperative PG cases; however, the lack of a standardized evaluation at our institution may be a confounding factor.…”
Section: Systemic Disease Associationsmentioning
confidence: 99%
“…Since then, it has been reported that about 7% of all patients with PG have concurrent malignant neoplasms (3). This data is based largely on case reports, which have linked PG to pediatric acute lymphoblastic leukemia, adult and pediatric AML, and myelodysplastic syndromes (3)(4)(5)(6)(7)(8). In one recently reported case, a patient presented with PG and was not found to have AML until his cutaneous lesions were evaluated (5).…”
Section: Discussionmentioning
confidence: 95%